Resenha de: Report of the Warren Commission on the assassination of President Kennedy - Franco, Guiomar Carvalho (Revista de História, 1965)
REPORT of the Warren Commission on the assassination of President Kennedy. New York, Bantam Books, 1964. xl, 728; pp. ilus. in-8. br.